Deductive content analysis of research on sustainable construction in India: current progress and future directions. (20th July 2019) - Goel, Ashish; Ganesh, L.S.; Kaur, Arshinder
Abstract: The rising construction output in India and its future potential, fuelled by rapid economic growth and socio-economic transitions, has necessitated sustainability integration into lifecycles of construction projects. The imperatives and implications of this integration transcend India's boundaries by influencing the global efforts in mitigating climate change and realizing the sustainable development goals. Yet, there is lack of studies that synthesize and critically evaluate the available literature to provide an overview of the current state of sustainable construction (SC) research in India and provide directions for future research. To this end, a systematic literature review (SLR) has been undertaken here using deductive content analysis. It reveals that the current SC research endeavours are predominantly oriented towards the macro-industry level, the environmental dimension and the internal stakeholders. Additionally, more emphasis has been provided on the final project deliverable compared to the project processes. Overall, this study makes three specific contributions: i) the current thrust areas of SC research in India have been identified while pointing out the imbalance in this academic pursuit; ii) a deductive content analysis framework has been developed that provides a generic template for conducting similar SLRs in the context of other countries; and iii) multiple research gaps have been identified and suggestions to design future studies are proposed based on extant SC literature, especially from similar developing economies. Therefore, despite its Indian focus, this review allows implications for other developing economies set for a similar socio-economic transition and growth in construction output. Highlights: Literature on sustainable construction in India is systematically reviewed. Existing research is predominantly focussed on environmental dimension. Research opportunities under social and economic dimensions are suggested. Need for holistic assessment of sustainability is highlighted. Indian scenario is compared with other large developing economies.